GAGASAN NEGARA REPUBLIK MENURUT TAN MALAKA DALAM NAAR DE REPUBLIEK INDONESIA - Suprianto, Edi; Montolalu, Johanis Josep; Tukiran, Antonius (Pineleng Theological Review, 2024)
This article discusses the idea of a republic according to Tan Malaka in Naar de Republiek Indonesia, written by the famous Indonesian thinker, Tan Malaka. In this article, the author presents Tan Malaka's thoughts through critical analysis of Tan Malaka's works. The aim is to examine Tan Malaka's thoughts as one of the phenomenal Indonesian thinkers and the Father of the Republic of Indonesia. This article wants to present the idea of a Republic that Tan Malaka envisioned for the Indonesian nation. One of his influential works is Naar de Republiek Indonesia. In his writing, Tan Malaka initiated the Republic as a form of the Indonesian state. The republic that Tan Malaka hopes for is a republic based on communism with democracy as the system for exercising power. With this form of state, Tan Malaka hopes that class differences that cause oppression can be overcome. Therefore, Tan Malaka made communism the ideology of the republic he aspired to and made the Indonesian Communist Party the main tool for achieving Indonesian independence. Even though it was not completely successful, Tan Malaka's contribution of thought ultimately gave inspiration to form the Republic of Indonesia. So, until now the form of the Indonesian state has become a Republic.